(untitled) (Journal of Science and Technology, 2016)
Alcoholic sorghum malt beverage, pito is a popular drink in Ghana, however it has a short shelflife of two days. In an attempt to extend its shelflife a study was carried out using malted sorghum. This was milled, mashed by single decoction and fermented by both lactic and ethanolic fermentation by resident microbes and pito wild yeast. The resulting product, pito was treated in two ways, first it was bottled, sodium metabisulphite added and pasteurized, this was coded PL. The second treatment involved filtration of yeast cells and pasteurization, this was coded NL. Bottled samples were stored for 2 months and analysis carried out on samples. Parameters monitored were pH, colour, specific gravity, alcohol content, degree of fermentation, extract content and energy. Sensory evaluation was also carried out on the samples. Results showed that pito can be processed, bottled and stored for about 2 months using one of the 2 treatments. However, the treatment involving PL was more efficient. Sensory results showed that the products were acceptable to the panelists.